The protective role of raltegravir in experimental acute lung injury in vitro and in vivo - Xu,Zehui (2022)
Disruption of pulmonary endothelial permeability and associated barrier integrity increase the severity of acute respiratory distress syndrome (ARDS). This study investigated the potential ability of the human immunodeficiency virus-1 (HIV-1) integrase inhibitor raltegravir to protect against acute lung injury (ALI) and the underlying mechanisms. Accordingly, the impact of raltegravir treatment on an in vitro lipopolysaccharide (LPS)-stimulated human pulmonary microvascular endothelial cell (HPMEC) model of ALI and an in vivo LPS-induced two-hit ALI rat model was examined. In the rat model system, raltegravir treatment alleviated ALI-associated histopathological changes, reduced microvascular permeability, decreased Evans blue dye extravasation, suppressed the expression of inflammatory proteins including HMGB1, TLR4, p-NF-κB, NLRP3, and MPO, and promoted the upregulation of protective proteins including claudin 18.1, VE-cadherin, and aquaporin 5 as measured via western blotting. Immunohistochemical staining further confirmed the ability of raltegravir treatment to reverse LPS-induced pulmonary changes in NLRP3, claudin 18.1, and aquaporin 5 expression. Furthermore, in vitro analyses of HPMECs reaffirmed the ability of raltegravir to attenuate LPS-induced declines in VE-cadherin and claudin 18.1 expression while simultaneously inhibiting NLRP3 activation and reducing the expression of HMGB1, TLR4, and NF-kB, thus decreasing overall vascular permeability. Overall, our findings suggested that raltegravir may represent a viable approach to treating experimental ALI that functions by maintaining pulmonary microvascular integrity.